RESERVATION OF GAS PIPELINE AS A MEANS OF INCREASING THE FUNCTIONAL RELIABILITY - and (Municipal economy of cities. Series: «Economy science», 2013)
We consider the redundancy, ie laying additional pipelines parallel to the principal as a way to improve the dependability of the system.